UPAYA MENINGKATKAN SIKAP KERJA SAMA SISWA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DENGAN MODEL COOPERATIVE LEARNING TIPE CARD SORT KELAS IV SEKOLAH DASAR - Muliyati, Maey; Zakiah, Linda; Usman, Herlina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Classroom Action Research (PTK) aims to increase student responsibility through the Numbered Head Together (NHT) learning model in Class IV. This research uses the Kemmis and Mc Taggart model with 4 steps, namely planning, implementation, observation and reflection. Data collection techniques come from questionnaires, observation of teacher and student actions. The data analysis technique uses simple quantitative by calculating the average achievement of student responsibility and descriptive qualitative to describe the results of the quantitative data obtained. In cycle I, the results of the student questionnaire that obtained > 75 were 61.29%. While in cycle II it reached 74.19% While Cycle III 90.32%. The data on teacher action observations in cycle I in improving student cooperation using the card sort type cooperative learning model reached 64%, while student activity obtained results of 62%. In cycle II, the observation of teacher activity actions reached 74% and student activity reached 69%. In cycle III, the observation of teacher actions reached 95%, while student activity was 90%. Thus, the use of the cooperative learning model of the card sort type can improve the cooperation of fourth grade students at SDN Bangka 07 Pagi in the Pancasila Education Subject.